Computational analysis of heat transfer in three types of motorcycle exhaust materials. (May 2020) - Tulus,; Marpaung, J.L.; Marpaung, T.J.; Suriati,
Abstract: The finite element method is one method used in the structural and nonstructural analysis. This paper aims to the simulated of the finite element method on nonstructural problems namely heat transfer. The media used has been a motorcycle exhaust system modeled with COMSOL Multiphysics 5.4 software by combining annealed stainless steel 405 with 35% chrome stainless steel, Beta-21S Titanium, and Carbon II type as a large tube on the exhaust model. The results of computing simulation obtained are that the lowest heat transfer value in Carbon II material type with a heat transfer rate of 325 K.